Solid Waste Management using GIS - Jawed, Aquib; Mandal, Anik; Sahana, Sudipta (International Journal of Computer Sciences and Engineering, 2020)
Uncontrolled growth of the urban population in developing countries in recent years has made solid waste management a crucial issue. Very often, a considerable amount of total expenditures is spent on the gathering of solid waste by city authorities. Optimization of the routing system for the gathering and transport of solid waste thus constitutes a crucial component of an efficient solid waste management system. This paper describes an attempt to design and develop an appropriate storage, collection and disposal plan for Kalyani, West Bengal State (India). A GIS optimal routing model is proposed to determine the location of dustbins in the Kalyani City, where citizens can look up for dustbins with capacity and type and can dump the garbage in it. The model uses dustbin type, dustbin location in the form of latitude and longitude and dustbin managing organization. The proposed model can be used by citizens to find the dustbins and it will promote cleanliness in the society.